A Hybrid Semi-implicit Method of 1D Transient Compressible Flow for Thermal-Hydraulic Analysis of (V)HTR Gas Turbine Systems - Wang, Jie; Cao, Xiaxin; Meng, Zhaoming; Wang, Jie; Ding, Ming (Frontiers in Energy Research, 2018)
Transient thermal-hydraulic analysis of (very) high temperature gas-cooled reactors gas turbine systems (HTRGTSs) needs system transient analysis codes. However, compared with the mature system transient thermal-hydraulic codes of pressurized water reactors (PWRs), the system analysis codes of HTRGTSs are not so fully developed. In this paper, a new hybrid semi-implicit (HSI) method is proposed based on the semi-implicit method and nearly-implicit method. In the HIS method, a new calculation strategy is devised: the convective term in treated explicitly to solve pressure and velocity, while density and temperature are solved in an implicit manner to get a convergent, stable and accurate solution in multiple transient scenarios. The HSI method was further validated via the shock-tube benchmark problem and verified via FLUENT simulations. In FLUENT simulations, outlet pressure transient, inlet mass flow transient and inlet temperature transients were studied. It was found that the HSI method is capable of capturing both the fast and slow compressible flow transients with good convergence and stability. Furthermore, an adaptive time step scheme is proposed for faster calculation, considering the maximum relative density difference and CFL condition.